Microbial Biofilm Colonizing Plastic Substrates in the Ross Sea (Antarctica): First Overview of Community-Level Physiological Profiles - Gabriella Caruso; Giovanna Maimone; Alessandro Ciro Rappazzo; Ombretta Dell’Acqua; Pasqualina Laganà; Maurizio Azzaro (Journal of Marine Science and Engineering, 2023)
The microbial colonization of plastic substrates made of polyvinylchloride (PVC) and polyethylene (PE) was studied in Tethys and Road Bays (Ross Sea, Antarctica) in order to evaluate the metabolic profiles of the plastisphere community in comparison with those of the surrounding waters. PVC and PE panels, mounted on stainless steel structures, were deployed in the austral summer 2017 at 5 and 20 m and recovered one year later at four different stations (Amorphous Glacier-AG was potentially impacted by the ice-melting process, and its control site was within Tethys Bay-TB; Road Bay-RB, close to the wastewater plant of the Italian research station Mario Zucchelli and its control site Punta Stocchino-PTS). Additional panels were settled in Road Bay at 5 m and recovered after three months to follow time variability in the microbial colonization process. At the same times and depths as plastic substrates, water samples were also collected. Carbon substrates’ utilization rates were determined on scraped microbial biofilm and water samples, with a fluorimetric assay based on 96-well Biolog Ecoplates. Complex carbon sources, carbohydrate and amines were the organic substrates that mostly fuelled the community metabolism in the RB area, while in the TB area, in addition to carbohydrates, phosphate carbon compounds and amino acids were also actively utilized. Within Road Bay, small differences in the physiological profiles were found, with higher metabolic rates in the biofilm community after 3 months’ deployment (late austral summer period) compared to 12 months, suggesting that autumn to spring period conditions negatively affected foulers’ metabolism. Moreover, different metabolic profiles between the plastisphere and the pelagic microbial community were observed; this last utilized a higher number of carbon sources, while plastic substrates were colonized by a more specialized community. Higher carbon substrate utilization rates were recorded at RB and AG stations, receiving organic supply from anthropic activity or ...